Multiple Ulcers Associated With Deep Vein Thrombosis Secondary to Herpes Zoster Infection of the Lower Limb - Makoto Kondo; Koji Habe; Keiichi Yamanaka (Clinical Case Reports)
ABSTRACT Persistent limb swelling and ulceration following herpes zoster may indicate the development of deep vein thrombosis, highlighting the importance of early diagnosis and initiation of anticoagulant therapy. Pain and reduced mobility are significant contributors to thrombosis, underscoring effective pain management's critical role in the prevention of deep vein thrombosis.